Plan de mejora para el egreso oportuno de pacientes vinculados al plan de atención domiciliaria atendidos en el servicio de urgencias en una institución de salud (2025)
The timely discharge of patients enrolled in a Home Care Plan (HCP) improves institution’s ability to optimize resources and enhance the quality of care and the patient’s quality of life. The institution under study (IUS) faces challenges with the timely discharge of patients linked to a HCP and an underreporting of patient data due to improper completion of the database for the Timely Discharge Program. Based on this, the objective of this descriptive study was to design an improvement plan for the timely discharge of patients enrolled in a home care plan and treated in the IUS's emergency department. The goal was to reduce prolonged hospital stays, improve bed turnover, optimize hospital resources, and enhance the quality of service and the quality of life for patients and their families. To achieve this, first, using the 2023 database, the causes preventing emergency department patients who are eligible for the home care plan from being discharged and enrolled in it were identified and analyzed. Subsequently, the illnesses most commonly found in patients enrolled in the IUS's home care plan were identified to guide the creation of the improvement plan. The results showed that the main reason patients were not discharged to a HCP was their refusal to enroll. Additionally, it was found that patients who did not experience timely discharge were older adults and insured under an EPS plan. Moreover, urinary tract infections were identified as one of the most common conditions among PAD-eligible patients in the institution. Based on these findings, an improvement plan was developed to enhance the Timely Discharge Program's effectiveness, increase patient enrollment, and ensure their timely discharge to a HCP. The plan also includes recommendations for its implementation, monitoring, and control.